Antistatic composite packaging material and preparation process thereof

Through multi-layer structure design and thermal pressing technology, the anti-static function is integrated, and the problem of weakening the effectiveness of existing anti-static packaging materials is solved, achieving the improvement of long-term anti-static and mechanical strength.

CN119408276APending Publication Date: 2025-02-11WUZHOU UNIV

Patent Information

Application Number
CN202411510055.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-28
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

Existing antistatic packaging materials can achieve antistatic effects in the short term, but over time, the effectiveness of coatings and antistatic agents gradually weakens, resulting in a significant decrease in the antistatic properties of packaging materials.

Method used

Using a multi-layer structural design, including substrate layer, metal oxide electrostatic absorption layer, metal foil layer, outer protective film and surface antistatic coating, the antistatic function is integrated through thermal pressing and coating technology, reducing the number of Reliability of the second coating.

Benefits of technology

It achieves a long-term anti-static effect, avoiding the problems of easy wear and decreased effectiveness of traditional anti-static coatings, ensuring that the material can maintain stable anti-static properties after long-term use, and significantly enhancing mechanical strength and durability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119408276A_ABST
    Figure CN119408276A_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of packaging materials, and discloses an antistatic composite packaging material and a preparation process thereof, the antistatic composite packaging material comprises: a base material layer, the base material layer is made of a polyester film or a hard paperboard material, and the base material layer is used as the bottommost layer of the composite material; the metal oxide static electricity absorption layer is made of aluminum oxide or an oxidation material; the metal foil layer is made of an aluminum foil material; a polyurethane protective film is adopted as the outer layer protective film; and the surface antistatic coating is made of a polytetrafluoroethylene material. Through the multi-layer structure design, the metal oxide static electricity absorbing layer (such as aluminum oxide or titanium oxide) and the metal foil conducting layer are adopted, and the long-acting antistatic effect is provided. By means of the design, the problems that a traditional antistatic coating is prone to abrasion and the efficacy is decreased progressively are solved, it is ensured that the material can still keep stable antistatic performance after being used for a long time, and the material is especially suitable for products needing to be stored and transported for a long time.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of packaging materials, in particular to an antistatic composite packaging material and a preparation process thereof. Background Art

[0002] In modern industry, many precision electronic devices and components are very sensitive to static electricity. Static electricity may not only damage electronic components, but also cause equipment failure, performance degradation, and even product scrapping. In order to solve this problem, a variety of antistatic packaging materials have appeared on the market, which are usually used for packaging electronic components, semiconductor chips, and precision instruments. However, existing antistatic packaging materials still have some significant deficiencies in practical applications, which restricts their widespread application and performance optimization.

[0003] Most of the existing antistatic packaging materials use antistatic coatings or add antistatic agents to the substrate. These methods can achieve antistatic effects in the short term, but the effectiveness of the coating and antistatic agent gradually weakens over time. The coating is easily affected by the environment (such as humidity, friction, etc.) during use and gradually loses its antistatic ability. After long-term storage or use, the antistatic performance of the packaging material decreases significantly, resulting in failure of product protection. Summary of the invention

[0004] In view of the deficiencies in the prior art, the present invention provides a composite packaging material with antistatic properties and a preparation process thereof, which solves the problem that most of the existing antistatic packaging materials use antistatic coatings or add antistatic agents to the substrate, which can achieve antistatic effects in the short term, but the effectiveness of the coatings and antistatic agents gradually weakens over time.

[0005] To achieve the above objectives, the present invention is implemented through the following technical solutions: a composite packaging material with antistatic properties, comprising:

[0006] A substrate layer, wherein the substrate layer is made of polyester film or hardboard material and is the bottom layer of the composite material and is located at the bottom of the entire structure;

[0007] A metal oxide static absorption layer, wherein the metal oxide static absorption layer is made of aluminum oxide or an oxidized material, and the metal oxide static absorption layer is directly coated on the surface of the substrate layer and is closely attached to the substrate layer;

[0008] A metal foil layer, wherein the metal foil layer is made of aluminum foil material and is closely attached to the metal oxide static absorbing layer and is located in the middle layer;

[0009] An outer protective film, wherein the outer protective film is a polyurethane protective film, and the outer protective film covers the metal foil layer and covers the entire composite material structure;

[0010] The surface antistatic coating is made of polytetrafluoroethylene material and is located on the outermost layer of the composite material, closely attached to the surface of the outer protective film.

[0011] Preferably, the thickness of the polyester film of the substrate layer is in the range of 0.5 to 0.6 mm, the thickness of the cardboard is in the range of 20 to 30 mm, the thickness of the metal oxide static absorbing layer is 0.2 to 0.3 microns, the thickness of the metal foil layer is 20 to 30 microns, the thickness of the outer protective film is 70 to 90 microns, and the thickness of the surface antistatic coating is 2 to 4 microns.

[0012] Preferably, a process for preparing a composite packaging material having antistatic properties comprises the following steps:

[0013] S1: Substrate surface pretreatment: cleaning, plasma treatment and electrostatic dust removal of the substrate;

[0014] S2: Metal oxide coating: coating a metal oxide electrostatically absorbing layer on the substrate surface and performing high-energy irradiation modification;

[0015] S3: Metal foil composite: composite the metal foil with the substrate;

[0016] S4: outer protective film coating: coating on the surface of the composite material;

[0017] S5: Surface treatment: spray antistatic coating on the outer protective film;

[0018] S6: Cutting and molding: cutting and molding the surface treated materials;

[0019] S7: Performance testing: Test the antistatic, mechanical strength and environmental resistance of the cut and formed materials.

[0020] Preferably, the substrate surface pretreatment step comprises:

[0021] Use isopropyl alcohol or deionized water to clean the substrate, the washing temperature is controlled at 40-60°C, and the duration is 3-5 minutes;

[0022] Ultrasonic assisted cleaning is used;

[0023] Use plasma equipment with a power of 50 to 70 W for surface activation, and the treatment time is 30 to 60 seconds;

[0024] Using electrostatic dust removal equipment, the voltage is set to 5000-8000V and the dust removal time is 10-20 seconds.

[0025] Preferably, the metal oxide coating step comprises:

[0026] Aluminum oxide or titanium oxide is coated on the surface of the substrate by chemical vapor deposition, and the coating thickness is 0.2 to 0.3 microns;

[0027] The coated substrate is cured in an environment of 200 to 220°C for 45 to 60 minutes;

[0028] The high-energy irradiation modification step uses ultraviolet rays with a wavelength of 200 to 300 nm, and the irradiation time is 10 to 30 seconds.

[0029] Preferably, the metal foil composite step comprises:

[0030] The metal foil is electropolished, the electrolyte temperature is 50-70°C, and the polishing time is 1-2 minutes;

[0031] Aluminum foil with a thickness of 20 to 30 microns is laminated to the substrate through a hot pressing process, the hot pressing temperature is 130 to 150°C, the pressure is 1 to 1.5 MPa, and the pressing time is 3 to 5 minutes;

[0032] An online bubble detection system is used with a bubble detection accuracy of 0.01 mm and the local heating temperature is controlled at 80-100°C for secondary pressing.

[0033] Preferably, the outer protective film coating step comprises:

[0034] Before lamination, use an electrostatic eliminator with a voltage of 6000-9000V for about 5-10 seconds;

[0035] The lamination is made of polyurethane film with a thickness of 70 to 90 microns, and the lamination temperature is controlled at 90 to 110°C;

[0036] After coating, the material is cooled to 5-10°C for about 2-3 minutes.

[0037] Preferably, the surface treatment step comprises:

[0038] Spraying a polytetrafluoroethylene antistatic coating with a thickness of 2 to 4 microns on the outer protective film;

[0039] After spraying, it is cured in an environment of 90-100°C, and the curing time is about 15-20 minutes.

[0040] Preferably, the cutting and forming step comprises:

[0041] The cutting tolerance is controlled at ±0.1 mm;

[0042] In the compression molding process, the mold temperature is 120-140°C, the pressure is 1.5-2MPa, the pressing time is about 2-4 minutes, and the molding error does not exceed 0.05 mm.

[0043] Preferably, the performance testing step includes:

[0044] In the antistatic performance test, the surface resistance of the material is controlled at 10^6~10^8 ohms;

[0045] The tensile strength of the material shall not be less than 15MPa, and the flexural strength shall not be less than 200MPa;

[0046] The temperature cycle test was carried out in an environment of -40℃ to +85℃, with a test cycle of about 48 hours. The mechanical strength and antistatic performance retention rate of the material was 95%.

[0047] The present invention provides a composite packaging material with antistatic properties and a preparation process thereof.

[0048] Beneficial effects:

[0049] 1. The present invention adopts a multi-layer structure design, a metal oxide static absorption layer (such as aluminum oxide or titanium oxide) and a metal foil conductive layer to provide a long-lasting antistatic effect. This design avoids the problem of easy wear and diminishing effectiveness of traditional antistatic coatings, ensuring that the material can still maintain stable antistatic performance after long-term use, and is particularly suitable for products that need to be stored and transported for a long time.

[0050] 2. The present invention significantly enhances the mechanical strength and durability of the packaging material by rationally selecting a substrate layer (such as polyester film or hardboard) and adding a metal foil layer to the material. The material can withstand high impact, pressure and friction, providing excellent protective performance, ensuring comprehensive protection of precision components during transportation and operation.

[0051] 3. The outer protective film in the composite material structure of the present invention is made of polyurethane material, which has good moisture resistance, wear resistance and weather resistance, and can maintain stable performance in harsh environments such as high temperature, low temperature and humidity. The antistatic performance and mechanical strength show excellent retention rates in different environments, ensuring that the packaging material can effectively protect the internal products under various working conditions.

[0052] 4. The preparation process of the present invention reduces multiple complex processes through hot pressing and coating technology, directly integrates the antistatic function into the multi-layer structure of the material, and no longer relies on multiple coatings of antistatic agents or conductive coatings, thereby significantly reducing production costs and improving manufacturing efficiency. This process is suitable for large-scale production and can achieve low-cost and high-efficiency production while ensuring performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0053] Figure 1 The present invention is a process flow chart for preparing an antistatic composite packaging material. DETAILED DESCRIPTION

[0054] The technical solution of the present invention will be described clearly and completely below in conjunction with the accompanying drawings of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0055] Please see attached Figure 1 The embodiment of the present invention provides an antistatic composite packaging material, comprising:

[0056] Composition of composite packaging materials

[0057] 1.1 Substrate layer

[0058] The substrate layer is the basic part of the composite packaging material and plays the main structural support role. The substrate layer can be made of polyester film (PET film) or cardboard. Polyester film has excellent mechanical strength, chemical resistance and heat resistance, and is suitable for lightweight and high-durability packaging needs. Cardboard is suitable for packaging scenarios that require stronger support and impact resistance, especially for the protection of large or fragile items. The substrate layer is located at the bottom of the entire composite material and provides basic support for other functional layers.

[0059] The thickness of polyester film is 0.5-0.6 mm. This thickness range ensures the flexibility and durability of the material.

[0060] The thickness of the hardboard is 20 to 30 mm, providing additional strength and impact protection.

[0061] 1.2 Metal oxide static absorption layer

[0062] The metal oxide static absorption layer is the core antistatic part of the composite material. This layer uses metal oxide materials such as aluminum oxide (Al2O3) or titanium oxide (TiO2), which have excellent ability to absorb and dissipate static electricity, effectively reducing static electricity accumulation. The metal oxide layer is directly covered on the surface of the substrate layer through a coating process and is tightly combined with the substrate layer to form a complete static barrier.

[0063] The thickness of the metal oxide layer is 0.2 to 0.3 microns, which can provide sufficient electrostatic protection without affecting the overall flexibility of the material.

[0064] 1.3 Metal foil layer

[0065] The metal foil layer uses highly conductive aluminum foil material, which is mainly used to quickly conduct static electricity and form an electromagnetic shield in the composite structure. This layer is located on top of the metal oxide layer, further enhancing the antistatic effect and protecting the internal electronic components from external electromagnetic interference.

[0066] The thickness of the metal foil layer is 20 to 30 microns, which ensures the electrical conductivity while keeping the material lightweight.

[0067] 1.4 Outer protective film

[0068] The outer protective film is made of polyurethane (PU) protective film, the main function of which is to protect the entire composite structure from the influence of the external environment, such as moisture, dust and physical wear. The polyurethane film has the characteristics of waterproof, moisture-proof and strong wear resistance, which prolongs the service life of the material while maintaining the overall strength and integrity of the material.

[0069] The thickness of the protective film: 70 to 90 microns, ensuring excellent protection without adding too much weight.

[0070] 1.5 Surface antistatic coating

[0071] The surface antistatic coating uses polytetrafluoroethylene (PTFE) material, which has excellent antistatic effect and excellent wear resistance and corrosion resistance. The coating is located on the outermost layer of the composite material, effectively preventing the accumulation and conduction of static electricity and protecting the inner structure from mechanical wear.

[0072] The thickness of the antistatic coating is 2 to 4 microns, which ensures the antistatic function without affecting the overall performance of the material.

[0073] A preparation process of a composite packaging material with antistatic properties, comprising the following steps:

[0074] S1. Substrate surface pretreatment

[0075] In order to ensure the close bonding between the metal oxide layer and the substrate, the substrate surface needs to be cleaned, plasma treated and electrostatically dusted. Cleaning can remove surface contaminants, plasma treatment enhances the adhesion of the substrate surface, and electrostatic dust removal eliminates residual static electricity and dust particles on the surface.

[0076] Cleaning temperature: 40-60°C, duration: 3-5 minutes.

[0077] Plasma power: 50-70W, processing time: 30-60 seconds.

[0078] Electrostatic dust removal voltage: 5000~8000V, processing time is 10~20 seconds.

[0079] S2. Metal oxide coating

[0080] A metal oxide layer is coated on the surface of the substrate, and aluminum oxide (Al2O3) or titanium oxide (TiO2) is evenly coated on the surface of the substrate by chemical vapor deposition (CVD). After coating, it is necessary to cure at a temperature of 200-220°C for 45-60 minutes to ensure the stability and firmness of the coating. The optional steps also include high-energy irradiation modification, using ultraviolet rays with a wavelength of 200-300nm to strengthen the coating, further improving the antistatic and wear resistance of the coating.

[0081] S3, Metal foil composite

[0082] After coating the metal oxide layer, the metal foil is composited with the substrate through a hot pressing process. Before hot pressing, the aluminum foil is electrolytically polished to improve its surface conductivity and smoothness. The polished aluminum foil passes through a hot pressing device at a temperature of 130-150°C, a pressure of 1-1.5 MPa, and a pressing time of 3-5 minutes to ensure a close bond with the substrate. In addition, online bubble detection is required to ensure the surface of the material is flat.

[0083] S4, outer protective film coating

[0084] The polyurethane protective film is covered on the surface of the composite material through hot melt lamination technology. Before lamination, a 6000-9000V static eliminator is used to remove surface static electricity to ensure uniform material adhesion during the lamination process. The lamination temperature is controlled at 90-110°C, and then the material is cooled to 5-10°C on a cooling table for 2-3 minutes to prevent deformation or peeling of the film layer.

[0085] S5. Surface treatment

[0086] Spray polytetrafluoroethylene antistatic coating on the outer protective film with a thickness of 2 to 4 microns, and evenly cover it through atomization spraying technology. After spraying, cure it in a 90100℃ environment for 1520 minutes to ensure that the coating is firmly attached and has good antistatic properties.

[0087] S6, cutting and forming

[0088] The processed materials are precisely cut with a cutting tolerance of ±0.1 mm. The molding temperature is 120-140°C, the pressure is 1.5-2MPa, the pressing time is 2-4 minutes, and the molding error does not exceed 0.05 mm, ensuring the accuracy and consistency of the finished material.

[0089] S7. Performance testing

[0090] The finished materials are strictly tested for antistatic, mechanical strength and environmental resistance.

[0091] Surface resistance range: 10^6~10^8 ohms.

[0092] Tensile strength: not less than 15MPa.

[0093] Flexural strength: not less than 200MPa.

[0094] Environmental resistance test: 48 hours of cycle test at temperatures from -40℃ to +85℃ to ensure that the material performance retention rate is 95%.

[0095] The following is an introduction in conjunction with specific embodiments:

[0096] Example 1: Antistatic packaging material for electronic components

[0097] Material composition:

[0098] Base material layer: 0.5 mm thick polyester film (PET film) is used, which has good flexibility and durability.

[0099] Metal oxide static-absorbing layer: Made of aluminum oxide (Al2O3), with a coating thickness of 0.3 microns, it has excellent static-absorbing properties.

[0100] Metal foil layer: Aluminum foil with a thickness of 20 microns is used to provide conductivity and electromagnetic shielding effect.

[0101] Outer protective film: A 70-micron thick polyurethane film covers the entire structure, providing protection against water, dust and wear.

[0102] Surface antistatic coating: A 3-micron thick polytetrafluoroethylene (PTFE) coating is used to ensure external antistatic protection.

[0103] Preparation process:

[0104] Cleaning treatment: The surface of the substrate was cleaned with ultrasonic assistance at a temperature of 50°C for 4 minutes.

[0105] Plasma treatment: Use a plasma device with a power of 60W for 45 seconds.

[0106] Metal oxide coating: Aluminum oxide was coated on the substrate by chemical vapor deposition (CVD) with a curing temperature of 210°C and a curing time of 50 minutes.

[0107] Metal foil composite: The aluminum foil is composited onto the substrate by hot pressing process, the hot pressing temperature is 140°C, the pressure is 1.2MPa, and the pressing time is 4 minutes.

[0108] Outer protective film lamination: Use hot melt lamination at 90°C and quickly cool at 5°C.

[0109] Surface antistatic coating: Spray polytetrafluoroethylene coating with a thickness of 3 microns and a curing time of 18 minutes.

[0110] Application: Used for packaging of high-precision electronic components, it can effectively prevent static electricity accumulation and protect sensitive components.

[0111] Example 2: Antistatic packaging material for precision instruments

[0112] Material composition:

[0113] Base material layer: 25mm thick hardboard is used to provide strong support and impact resistance.

[0114] Metal oxide static-absorbing layer: Made of titanium oxide (TiO2), with a coating thickness of 0.25 microns, it can effectively absorb static electricity.

[0115] Metal foil layer: Aluminum foil with a thickness of 30 microns is used to ensure higher conductivity and shielding performance.

[0116] Outer protective film: 80 micron thick polyurethane film, providing high mechanical strength and environmental resistance.

[0117] Surface antistatic coating: Spray polytetrafluoroethylene (PTFE) coating with a thickness of 4 microns.

[0118] Preparation process:

[0119] Cleaning: Use deionized water to clean at 45°C for 3 minutes.

[0120] Plasma treatment: power is 50W, treatment time is 30 seconds.

[0121] Metal oxide coating: Titanium oxide was coated using a CVD process with a curing temperature of 200°C and a curing time of 45 minutes.

[0122] Metal foil composite: hot pressing temperature is 150°C, pressure is 1.5MPa, and pressing time is 5 minutes.

[0123] Outer protective film coating: The coating process is carried out at a temperature of 100°C and a cooling temperature of 10°C.

[0124] Surface antistatic coating: Spray polytetrafluoroethylene with a thickness of 4 microns and a curing time of 20 minutes.

[0125] Application: Suitable for outer packaging of precision instruments to ensure antistatic protection during transportation and storage while preventing mechanical damage.

[0126] Example 3: Antistatic packaging material for semiconductor chips

[0127] Material composition:

[0128] Base material layer: 0.6mm thick polyester film is used to provide a lightweight and high-strength foundation.

[0129] Metal oxide static absorption layer: Aluminum oxide is used with a coating thickness of 0.2 microns.

[0130] Metal foil layer: Aluminum foil with a thickness of 25 microns was used.

[0131] Outer protective film: Made of 90 micron thick polyurethane film, it has extremely high protection capabilities.

[0132] Surface antistatic coating: Spraying polytetrafluoroethylene coating with a thickness of 2 microns.

[0133] Preparation process:

[0134] Cleaning: Use deionized water to clean at 55°C for 4 minutes.

[0135] Plasma treatment: power is 65W, treatment time is 40 seconds.

[0136] Metal oxide coating: Aluminum oxide coating, curing temperature is 220℃, time is 60 minutes.

[0137] Metal foil composite: hot pressing temperature is 135°C, pressure is 1MPa, and pressing time is 3 minutes.

[0138] Outer protective film coating: Use 95℃ for coating and 5℃ for cooling.

[0139] Surface antistatic coating: Spray polytetrafluoroethylene with a thickness of 2 microns and a curing time of 15 minutes.

[0140] Application: It is particularly suitable for the packaging of semiconductor chips and sensitive electronic components. It can effectively reduce the damage of static electricity to chips and improve the overall safety of packaging.

[0141] Table 1 Performance test table of different embodiments:

[0142]

[0143]

[0144] Table field explanation:

[0145] Antistatic performance (Ohm):

[0146] This field indicates the surface resistance of the material, which is used to measure the antistatic effect of the material. The unit is ohm (Ω), and the value is between 10^6 and 10^8 ohms. The smaller the value, the stronger the antistatic performance.

[0147] Tensile strength (MPa):

[0148] This field indicates the tensile strength of the material, that is, the maximum tensile force that the material can withstand during stretching, in megapascals (MPa). The higher the tensile strength, the less likely the material is to break, indicating that it has higher mechanical strength.

[0149] Flexural strength (MPa):

[0150] This field indicates the flexural strength of the material, which is the material's ability to resist bending, in megapascals (MPa). Materials with higher flexural strength are suitable for applications that require bending loads.

[0151] Environmental resistance (retention rate %):

[0152] This field indicates the retention rate of the antistatic performance and mechanical strength of the material after the temperature cycle test. The value indicates the performance stability of the material in harsh environments (such as high and low temperatures, humid conditions). The higher the value, the better the environmental resistance of the material, and the unit is percentage (%).

[0153] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A composite packaging material with antistatic properties, characterized in that: include: A substrate layer, wherein the substrate layer is made of polyester film or hardboard material and is located at the bottom of the composite material and is located at the bottom of the entire structure; A metal oxide static absorption layer, wherein the metal oxide static absorption layer is made of aluminum oxide or an oxidized material, and the metal oxide static absorption layer is directly coated on the surface of the substrate layer and is closely attached to the substrate layer; A metal foil layer, wherein the metal foil layer is made of aluminum foil material and is closely attached to the metal oxide static absorbing layer and is located in the middle layer; An outer protective film, wherein the outer protective film is a polyurethane protective film, and the outer protective film covers the metal foil layer and covers the entire composite material structure; The surface antistatic coating is made of polytetrafluoroethylene material and is located on the outermost layer of the composite material, closely attached to the surface of the outer protective film.

2. The antistatic composite packaging material according to claim 1, characterized in that: The thickness of the polyester film of the substrate layer is in the range of 0.5 to 0.6 mm, the thickness of the hardboard is in the range of 20 to 30 mm, the thickness of the metal oxide static absorbing layer is in the range of 0.2 to 0.3 μm, the thickness of the metal foil layer is in the range of 20 to 30 μm, the thickness of the outer protective film is in the range of 70 to 90 μm, and the thickness of the surface antistatic coating is in the range of 2 to 4 μm.

3. A process for preparing an antistatic composite packaging material, characterized in that: The antistatic composite packaging material according to any one of claims 1 to 2 comprises the following steps: S1. Substrate surface pretreatment: cleaning, plasma treatment and electrostatic dust removal of the substrate; S2, metal oxide coating: coating a metal oxide static-absorbing layer on the surface of the substrate and performing high-energy irradiation modification; S3, metal foil composite: composite the metal foil with the substrate; S4, outer protective film coating: coating on the surface of the composite material; S5. Surface treatment: spray antistatic coating on the outer protective film; S6, cutting and molding: cutting and molding the surface treated materials; S7. Performance testing: Test the antistatic, mechanical strength and environmental resistance of the cut and formed materials.

4. The process for preparing the antistatic composite packaging material according to claim 3, characterized in that: The substrate surface pretreatment step comprises: Use isopropyl alcohol or deionized water to clean the substrate, the washing temperature is controlled at 40-60°C, and the duration is 3-5 minutes; Ultrasonic assisted cleaning is used; Use plasma equipment with a power of 50 to 70 W for surface activation, and the treatment time is 30 to 60 seconds; Using electrostatic dust removal equipment, the voltage is set to 5000-8000V and the dust removal time is 10-20 seconds.

5. The process for preparing the antistatic composite packaging material according to claim 3, characterized in that: The metal oxide coating step comprises: Aluminum oxide or titanium oxide is coated on the surface of the substrate by chemical vapor deposition, and the coating thickness is 0.2 to 0.3 microns; The coated substrate is cured in an environment of 200 to 220°C for 45 to 60 minutes; The high-energy irradiation modification step uses ultraviolet rays with a wavelength of 200 to 300 nm, and the irradiation time is 10 to 30 seconds.

6. The process for preparing the antistatic composite packaging material according to claim 3, characterized in that: The metal foil compounding step comprises: The metal foil is electropolished, the electrolyte temperature is 50-70°C, and the polishing time is 1-2 minutes; Aluminum foil with a thickness of 20 to 30 microns is laminated to the substrate through a hot pressing process, the hot pressing temperature is 130 to 150°C, the pressure is 1 to 1.5 MPa, and the pressing time is 3 to 5 minutes; An online bubble detection system is used with a bubble detection accuracy of 0.01 mm and the local heating temperature is controlled at 80-100°C for secondary pressing.

7. The process for preparing the antistatic composite packaging material according to claim 3, characterized in that: The outer protective film laminating step comprises: Before lamination, use an electrostatic eliminator with a voltage of 6000-9000V for about 5-10 seconds; The lamination is made of polyurethane film with a thickness of 70 to 90 microns, and the lamination temperature is controlled at 90 to 110°C; After coating, the material is cooled to 5-10°C for about 2-3 minutes.

8. The process for preparing the antistatic composite packaging material according to claim 3, characterized in that: The surface treatment step comprises: Spraying a polytetrafluoroethylene antistatic coating with a thickness of 2 to 4 microns on the outer protective film; After spraying, it is cured in an environment of 90-100°C, and the curing time is about 15-20 minutes.

9. The process for preparing the antistatic composite packaging material according to claim 3, characterized in that: The cutting and forming step comprises: The cutting tolerance is controlled at ±0.1 mm; In the compression molding process, the mold temperature is 120-140°C, the pressure is 1.5-2MPa, the pressing time is about 2-4 minutes, and the molding error does not exceed 0.05 mm.

10. The process for preparing the antistatic composite packaging material according to claim 3, characterized in that: The performance testing step comprises: In the antistatic performance test, the surface resistance of the material is controlled at 10^6~10^8 ohms; The tensile strength of the material shall not be less than 15MPa, and the flexural strength shall not be less than 200MPa; The temperature cycle test was carried out in an environment of -40℃ to +85℃, with a test cycle of about 48 hours. The mechanical strength and antistatic performance retention rate of the material was 95%.

Citation Information

Patent Citations

  • Method for preparing antistatic coating for polyester film or sheet

    CN102115544A

  • Anti-static coating liquid, anti-static protective film and preparation of anti-static protective film

    CN118359987A

  • Antistatic packaging film capable of preventing powder adsorption

    CN221339808U

  • Transparent antistatic packing material and packing bag using packing material

    JP2019023102A

Cited By

  • Anti-static polyester film and preparation method thereof

    CN120716130A